Analysis of a Permanent Magnet Eddy Current Heater Driven by a Wind Turbine - TUDORACHE, T. (Advances in Electrical and Computer Engineering, 2015)
This paper deals with the numerical analysis and optimal design of a Permanent Magnet Eddy Current Heater (PMECH) driven by a wind turbine. This study includes a preliminary sizing of the wind turbine, an optimal design of the PMECH from cost reduction point of view, a heat transfer analysis of the device and a study of the dynamic response of the wind system. The electromagnetic and heat transfer analysis is based on Finite Element Method (FEM) implemented in the Flux software package and the dynamic response of the wind system is analyzed using a dedicated model developed under Matlab/Simulink environment.